Mathematical analysis of nano-fuel flow and heat transfer mechanism in an automobile’s exhaust catalytic converter - Chokoe, Itumeleng Gift (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMil)--Stellenbosch University, 2025.